Pengaruh Motivasi, Kompetensi, dan Gaya Kepemimpinan Terhadap Kinerja Prajurit Bekangdam IV/Diponegoro - Dimas Aditya Ambarwanto; Kasmari Kasmari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the influence of motivation, competence and leadership style on the performance of Bekangdam IV/Diponegoro Soldiers. The method used is quantitative with a type of field research. Through the accidental sampling technique, a sample of 72 soldiers was obtained. The data sources for this research are divided into primary data sources in the form of questionnaires and secondary data sources, namely documents in the form of additional data during the research. Data was collected through observation, documentation and questionnaires which became research instruments. Data was collected and then analyzed through multiple linear regression analysis and hypothesis testing. The results of the research state that Motivation, competency, and leadership style have a positive and significant effect on the performance of Bekangdam IV/Diponegoro Soldiers. The leadership style applied by the leader is a motivational type.